Conceptualizing Grade Inflation - Adam Tyner; Seth Gershenson (Institute of Labor Economics (IZA), 2020)
Evidence of grade inflation in U.S. high schools is often misinterpreted due to confusion about how grade inflation is, or should be, defined. This note clarifies the implications of recent research on grade inflation in two ways. First, we situate the evidence by defining three distinct types of grade inflation. Second, we extend past research using data from North Carolina by documenting the different types of grade inflation experienced by high school students in the state over a recent ten-year period. Static grade inflation has been, and remains, higher in schools serving relatively disadvantaged student populations; however, differential growth in grade inflation in schools serving relatively advantaged student populations over the past 10 years has significantly narrowed this SES-based gap in grade inflation.
Keywords: I26; Q54; 330; grade inflation; achievement gaps; grading standards